Artificial intelligence and its impact on the Peruvian labor market - Cornejo Cachay, Diego Leonel (2023)
The development of artificial intelligence (AI), as a global advance, implies the social transformation towards a new paradigm, with great influence in various fields, such as labor. Thus, the Peruvian labor market has changed as a consequence of an inevitable process. For this reason, it is important to know the new way of handling labor relations and the significant changes that occur in the various economic sectors of our country as a result of the influence of AI, in order to define the creation of a special regulatory text as a viable option to cover different aspects related to the scenario.